A grounding zone wedge origin for the Palaeoproterozoic Makganyene Formation of South Africa - D. P. Le Heron; M. E. Busfield; A. J. B. Smith; S. Wimmer (Frontiers in Earth Science, 2022)
The Makganyene Formation is a Siderian (2.45–2.22 Ga) diamictite-dominated succession, with both outcrop and subcrop in the Griqualand West Basin of the Transvaal Group of South Africa. We provide new outcrop and core descriptions from this succession, supplemented by microscopic analyses, to present an updated depositional model for a classic Palaeoproterozoic diamictite. Although internal correlation of core and outcrop successions is not possible, a recurring pattern is observed where diamictites are organised into coarsening-upward motifs at the tens of metres scale. With additional finds of striated clasts, and evidence for dropstones both at the core scale and at the microscopic scale, earlier interpretations of glacial control on sedimentation can be substantiated, with modification of glacial diamictites by mass flow processes also recognised. Overall, given the characteristic progradational stratigraphic architecture, we propose a new model for the Makganyene Formation which is considered to represent deposition of a grounding zone wedge at an ancient, oscillating ice margin.